Pengaruh Sektor Pertambangan Dan Penggalian Terhadap Produk Domestik Regional Bruto Kabupaten Banggai: The Influence of the Mining And Quarrying Sector on the Gross Regional Domestic Product of Banggai Regency - Abd. Rauf R.A Barri; Suwardi Zakaria; Taufik Bidullah (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2021)
The results of this study show the regression equation, namely Y = 7927045.556 + 2.128 X; in the equation, it can be seen that the X value is 2,128 (positive), which means that if the mining and quarrying sector increases, then the PDRB of Banggai Regency will also increase and if the mining and quarrying sector is equal to zero (0) then the PDRB of Banggai Regency will decrease by 7927045.556. The magnitude of the correlation coefficient (R) obtained is 0.991; the relationship between the mining and quarrying sectors and the GDP is very strong because it is at an interval of 0.80-1.000. Based on the results of the thing test, judging from the t-test, the value obtained, namely thing > table or 14,494 > 2,776, means that the mining and quarrying sector has a positive and significant effect on the Gross Regional Domestic Product (PDRB) of Banggai Regency.